Comparison of Two Methods for Numerical Upscaling - KLIMCZAK, Marek; CECOT, Witold (Engineering Transactions, 2016)
The main objective of this paper is to compare two discretization-based homogenization methods. A local numerical homogenization and a multiscale finite element method (MsFEM) are first briefly presented and next numerically tested. In the case of MsFEM, a new shape function construction is also presented. Extensive comparison of both techniques constitutes the main part of this study. Novelty of this research is to combine forementioned methods with mesh adaptivity at the coarse mesh level and the application of the higher-order approximation.